Pilgrimage and the Prehistory of Landscape - Restuccia, Francesco (Aisthesis, 2025)
According to Joachim Ritter, aesthetic sensitivity to landscape arose in the modern age as a response to and a remedy for the objectivation of nature and its alienation from subjectivity. The appreciation of a landscape would compensate for the loss of the holistic relationship with nature that characterized the ancient theoretical worldview. Although Ritter’s theory allows us to account for both elements of continuity and discontinuity in the transformation of our relationship with nature, the way he refers to an indeterminate conception of the totality of the Universe, valid from Antiquity to the Middle Ages, is questionable. This article suggests that, prior to modernity, a non-instrumental approach to nature could be found in the practice of Christian pilgrimage, thanks to its experiential dimension. The origin of landscape could be identified in the secularization of the Franciscan experience of nature as a figure of heaven.